2009
DOI: 10.1590/s0074-02762009000800003
|View full text |Cite
|
Sign up to set email alerts
|

Morphological study of the eggs and nymphs of Triatoma dimidiata (Latreille, 1811) observed by light and scanning electron microscopy (Hemiptera: Reduviidae: Triatominae)

Abstract: Eggs and nymphs of Triatoma dimidiata were described using both light and scanning electron microscopy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…This characteristic was also observed in T. pseudomaculata [20]. These organisms also share characteristics of egg morphology [21] and karyotypic, since all have 22 chromosomes [20,22,23].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…This characteristic was also observed in T. pseudomaculata [20]. These organisms also share characteristics of egg morphology [21] and karyotypic, since all have 22 chromosomes [20,22,23].…”
Section: Discussionsupporting
confidence: 55%
“…This characteristic was also observed in T. klugi [24], T. maculata [20] and T. melanosoma [25]. T. maculata, T. sherlocki, and T. melanosoma also share characteristics of egg morphology [21]. Furthermore, all species have the diploid chromosome set 2n = 22A (20A + XY) [20,22,25].…”
Section: Discussionmentioning
confidence: 61%
“…Furthermore, Nascimento et al [ 55 ] also observed similarities between spermathecae morphology from P. lignarius, P. megistus and P. tibiamaculatus comb. nov., and Mello et al [ 56 ] recorded a relationship between exocorial cells in eggs of P. tibiamaculatus comb. nov. with Panstrongylus .…”
Section: Discussionmentioning
confidence: 99%
“…The descriptions herein are the first available from Mexico on T. rubida and T. mexicana in terms of egg ornamentation, while T. dimidiata eggs have been described for a Veracruz population (Mello et al 2009). It is worth stressing that there is a strong morphological and chromatic variation between populations of this species, and egg morphology is a useful trait given its wide distribution.…”
Section: Discussionmentioning
confidence: 99%